Methylene blue-photodynamic therapy for Microsporum canis infection: investigating a dual mechanism of fungicidal action and neutrophil homeostasis restoration - Zhang, Xinyu; Peng, Gaoyuan; Pan, Kaisu; Qin, Shulei; Xu, Weilun; Huang, Lan; Liao, Liuwei; Lu, Qian; Huang, Qihua; Haotian, Shao; Zheng, Dongyan; Cao, Cunwei (Frontiers in Microbiology, 2025)
BackgroundMicrosporum canis is an increasingly common cause of tinea capitis. Conventional antifungal therapies are limited by toxicity and resistance, creating a need for novel treatments. Antimicrobial photodynamic therapy (aPDT) is a promising alternative. We investigated the efficacy and dual mechanism of methylene blue-photodynamic therapy (MB-PDT) against M. canis, focusing on its effects on the host innate immune response.MethodsThe in vitro susceptibility of clinical M. canis isolates was determined by broth microdilution. Fungal ultrastructural changes were examined using transmission electron microscopy. In vivo efficacy was assessed in a murine dermatophytosis model and compared to topical terbinafine. Systemic immunomodulatory effects were evaluated by flow cytometric analysis of peripheral blood neutrophil phenotypes (Dectin-1, Dectin-2) and functional markers (MPO, NOX2).ResultsIn vitro, MB-PDT demonstrated potent fungicidal activity (Geometric Mean MIC at 80 J/cm2: 0.367 μg/mL; 95% CI: 0.295–0.439 μg/mL). It induced severe ultrastructural damage, including mitochondrial collapse and cell wall disruption. In the murine model, MB-PDT achieved an 80% mycological cure rate, significantly outperforming topical terbinafine (20% cure rate). Mechanistically, M. canis infection induced systemic neutrophil dysfunction, evidenced by a population shift and suppressed MPO and NOX2 expression. MB-PDT treatment reversed this immune dysfunction, restoring neutrophil homeostasis and the expression of key functional markers (MPO, NOX2).ConclusionMB-PDT is a highly effective treatment for M. canis infection. Its efficacy is based on a dual mechanism: direct fungicidal action through oxidative damage and restoration of host neutrophil function.